2016
DOI: 10.1097/mib.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinical and Genetic Parameters Associated with Hidradenitis Suppurativa in Inflammatory Bowel Disease

Abstract: HS is present in 6.8% to 10.6% of IBD patients. Co-morbid HS is associated with an early onset of IBD in which anti-tumor necrosis factor-α therapy and surgical resections are often needed. We identified a suggestive protective association with ELOVL7 and suggestive risk association with the genes SULT1B1 and SULT1E1 for HS, in the context of IBD. These genetic associations need further exploration and replication in additional independent cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…The increased rate of IBD and HS in the younger and African‐American population may suggest that a genetic component may play an important role in the pathogenesis of disease in these patient populations as compared to those with IBD alone. This is supported by studies identifying a potential genetic link between the two diseases . Such patients may also be at particularly high risk of morbidity if exposed to environmental factors such as smoking.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The increased rate of IBD and HS in the younger and African‐American population may suggest that a genetic component may play an important role in the pathogenesis of disease in these patient populations as compared to those with IBD alone. This is supported by studies identifying a potential genetic link between the two diseases . Such patients may also be at particularly high risk of morbidity if exposed to environmental factors such as smoking.…”
Section: Discussionmentioning
confidence: 87%
“…This is supported by studies identifying a potential genetic link between the two diseases. 12 Such patients may also be at particularly high risk of morbidity if exposed to environmental factors such as smoking.…”
Section: Unregulated Inflammation and Immune Dysregulation Have Beenmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, associations between hidradenitis suppurativa or dissecting cellulitis of the scalp with pyoderma gangrenosum are not infrequent [14]. A recent study demonstrated the association between hidradenitis suppurativa and the inflammatory bowel disease, especially Crohn's disease [15]. …”
Section: Discussionmentioning
confidence: 99%